1967
DOI: 10.1111/j.2044-8279.1967.tb01950.x
|View full text |Cite
|
Sign up to set email alerts
|

AN EXPERIMENT ON MULTIPLE‐CHOICE VERSUS OPEN‐ENDED ANSWERING IN A VOCABULARY TEST

Abstract: Summary. An experiment was conducted in which the results of multiple‐choice and open‐ended techniques were compared on a test of vocabulary (Test E of the Self‐judging Vocabulary Scale). The subjects were two groups, each consisting of fifty naval ratings, equated on intelligence test AH 4. Group M took the vocabulary test in its multiple‐choice form immediately followed by the same test in open‐ended form; for Group O, the order was reversed. Significant differences were found between multiple‐choice and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Inconsistent findings reresponse format. To control for the retention effect sulted in similar comparisons between the keylist inherent in a study by Heim and Watts (1967) who and multiple-choice completion formats. The keyused items measuring verbal skills, Traub and Fisher list format was relatively easy in terms of the peradministered items rewritten in the multiple-choice centage of possible points achieved by examinees, format two weeks later.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent findings reresponse format. To control for the retention effect sulted in similar comparisons between the keylist inherent in a study by Heim and Watts (1967) who and multiple-choice completion formats. The keyused items measuring verbal skills, Traub and Fisher list format was relatively easy in terms of the peradministered items rewritten in the multiple-choice centage of possible points achieved by examinees, format two weeks later.…”
Section: Introductionmentioning
confidence: 99%
“…They question whether MC testing produces invalid results, or rather less conclusive results, than constructed-response exams. Bridgemann and Rock's (1992) study on college admittance testing, however, found otherwise; and other studies that compare essay exams and MC tests also show a high correlation between the two as student measurement tools (Bennet, Rock, & Wang, 1990;Bracht & Hopkins, 1970;Bridgeman & Rock, 1993;Heim & Watts, 1967;Joorabchi & Chawhan, 1975;Patterson, 1926;Traub & Fisher, 1977;Traub, 1993;Ward, 1982).…”
Section: Multiple-choice (Mc) Items Were Introduced In the Armymentioning
confidence: 99%
“…Early work comparing multiple-choice tests with constructed-response tests (Davis & Fifer, 1959;Heim & Wats, 1967;Vemon, 1962) generally indicated that tests employing different formats cannot be expected to have the same means, standard deviations, and correlations with criterion variables. Some of these differences can be assumed to be due to changes in the scale of measurement and amount of error variance associated with each format.…”
mentioning
confidence: 99%